Plant Mitochondria Methods and Protocols - Whelan, James.; Whelan, James.; Murcha, Monika W.; Murcha, Monika W. (Methods in Molecular Biology,, 2015)
The chapters compiled in this detailed collection outline a number of methods used to study plant mitochondria today, starting from the isolation of mitochondria to detailed analyses of RNA, protein, and enzymatic activities. Given that the ability to uncover mitochondria’s unique features is underpinned by current methodology, this book explores the subject from morphology to detailed molecular mechanisms. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Practical and authoritative, Plant Mitochondria: Methods and Protocols serves as a vital resource to beginners in the field as well as to expert researchers who find themselves being pulled into the field of mitochondrial research as it links to so many important aspects of plant cell biology.